Optimal capacitor placement by using CAPO application and bus ranking methodology: article / Muhammad Firdaus Samidun - Samidun, Muhammad Firdaus (2011)
Transfer of electrical energy from the source of generation to the customer via the transmission and distribution networks is accompanied by losses. The majority of these losses occur on the distribution system. It is widely recognized that placement of shunt capacitors on the distribution system can lead to a reduction in power losses, improve voltage profile and release system capacity. Reduction of I2R loss in distribution systems is very essential to improve the overall efficiency of power delivery. The I R loss can be separated into two parts based on the active and reactive power components of branch currents. This thesis work presents a method of minimizing the loss associated with reactive component of branch currents by placing shunt capacitors. The methods that use are Capacitor Placement Optimization (CAPO) and Bus ranking method. The performance of the proposed method was investigated on distribution systems consisting 9 buses and it was found that a significant loss saving can be achieved by placing optimal capacitors in the system. This method has been implemented using Digsilent software. Digsilent is used to model, simulate, and analyze network in distribution system. The effect of using Bus ranking and CAPO method will show in this network within the result based on minimum voltage and total power losses. The result shows that by installing capacitor at suitable location with an appropriate sizing by using CAPO method there will be lower total power losses and higher voltage level in the distribution network. CAPO method gives better performance rather than Bus ranking method.